Comparative Study of Halogen‐ and Hydrogen‐Bond Interactions between Benzene Derivatives and Dimethyl Sulfoxide. Issue 12 (26th June 2015) - Zheng, Yan‐Zhen; Deng, Geng; Zhou, Yu; Sun, Hai‐Yuan; Yu, Zhi‐Wu
Abstract The halogen bond, similar to the hydrogen bond, is an important noncovalent interaction and plays important roles in diverse chemistry‐related fields. Herein, bromine‐ and iodine‐based halogen‐bonding interactions between two benzene derivatives (C6F5Br and C6F5I) and dimethyl sulfoxide (DMSO) are investigated by using IR and NMR spectroscopy and ab initio calculations. The results are compared with those of interactions between C6F5Cl/C6F5H and DMSO. First, the interaction energy of the hydrogen bond is stronger than those of bromine‐ and chlorine‐based halogen bonds, but weaker than iodine‐based halogen bond. Second, attractive energies depend on 1/rn, in which n is between three and four for both hydrogen and halogen bonds, whereas all repulsive energies are found to depend on 1/r8.5. Third, the directionality of halogen bonds is greater than that of the hydrogen bond. The bromine‐ and iodine‐based halogen bonds are strict in this regard and the chlorine‐based halogen bond only slightly deviates from 180°. The directional order is iodine‐based halogen bond>bromine‐based halogen bond>chlorine‐based halogen bond>hydrogen bond. Fourth, upon the formation of hydrogen and halogen bonds, charge transfers from DMSO to the hydrogen‐ and halogen‐bond donors. The CH3 group contributes positively to stabilization of the complexes.